James L. Pearson, Shamanism and the Ancient Mind: A Cognitive Approach to Archaeology - Hill, David (Pomegranate, 2007)
James L. Pearson, Shamanism and the Ancient Mind: A Cognitive Approach to Archaeology (Lanham, MD: AltaMira Press, 2002), ix + 198 pp., 72 (cloth), 27.95 (paper)